Stretching Exercise versus Local Corticosteroid Injection in Plantar Fasciitis: A Comparative Study - Gurung, Sandeep; DC, Gopal Sagar; Pant, Biswas (Journal of Nepalgunj Medical College, 2021)
Introduction: Plantar fasciitis is an inflammatory painful condition, one of the most common causes of heel pain. The cause of it is multifactorial; and different treatment modalities are available.Aims:To compare the effectiveness between the stretching exercise and corticosteroid injection.Methods:This study was conducted at Nepalgunj medical college, in the department of orthopedics from September 2019 to September 2020. Patients were equally divided into two groups. In Group A corticosteroid injection was given and in group B stretching exercise was advised. Patients were followed up at two weeks, 8weeks and 16weeks; pretreatment and post-treatment pain level was assessed by Visual Analog Scale (VAS) and Functional outcome was assessed by Foot and Ankle Ability Measure (FAAM) Scale.Results: Both groups were comparable in relation to age and sex. There was significant decrease in pain and improvement of function in steroid group at two weeks and eight weeks follow up; whereas at 16weeks follow up plantar fascia stretching groups improved significantly.Conclusion: For short term relief local corticosteroid injection is superior; but for long term relief in pain and improvement in function plantar fascia stretching exercise is better treatment option.